The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1371/journal.pbio.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Regulated RalBP1 Binding to RalA and PSD-95 Controls AMPA Receptor Endocytosis and LTD

Abstract: A two step mechanism was identified that regulates receptor endocytosis during the development of long-term depression (LTD), a long-lasting decrease in synaptic transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 56 publications
(66 reference statements)
2
63
0
1
Order By: Relevance
“…LTD is impaired by RNAi knockdown or genetic disruption of PSD-95 in mice, and it can be enhanced by PSD-95 overexpression (Migaud et al 1998;Beique and Andrade 2003;Stein et al 2003;Ehrlich et al 2007;Carlisle et al 2008;Xu et al 2008). Activity-dependent dephosphorylation of PSD-95 (leading to destabilization of PSD-95 in the PSD), and PSD-95-mediated interactions with key signaling proteins (such as AKAP79/150 and protein phosphatases), may underlie the importance of PSD-95 in LTD Xu et al 2008;Bhattacharyya et al 2009;Han et al 2009). …”
Section: Psd-95mentioning
confidence: 99%
“…LTD is impaired by RNAi knockdown or genetic disruption of PSD-95 in mice, and it can be enhanced by PSD-95 overexpression (Migaud et al 1998;Beique and Andrade 2003;Stein et al 2003;Ehrlich et al 2007;Carlisle et al 2008;Xu et al 2008). Activity-dependent dephosphorylation of PSD-95 (leading to destabilization of PSD-95 in the PSD), and PSD-95-mediated interactions with key signaling proteins (such as AKAP79/150 and protein phosphatases), may underlie the importance of PSD-95 in LTD Xu et al 2008;Bhattacharyya et al 2009;Han et al 2009). …”
Section: Psd-95mentioning
confidence: 99%
“…2C). 77 Surprisingly, Ral activation downstream of N-methyl-D-aspartate receptor (NMDAR) stimulation leads to removal of AMPARs from the cell surface. 78 Indeed, Ral is a bi-directional regulator of membrane traffic. When associated with the exocyst complex, Ral mediates the polarized delivery of vesicles toward the plasma membrane.…”
Section: The Role Of Small Gtpases and Recycling Endosomes In Neuronamentioning
confidence: 99%
“…During NMDAR-LTD, Ca 2C influx leads to Ral activation and recruitment of RalBP1 to spines. 78 NMDAR stimulation simultaneously activates a phosphatase called PP1, which dephosphorylates RalBP1, allowing its association with the scaffolding protein PSD-95. The close proximity of the AMPARs in complex with PSD-95 and endocytic proteins bound to RalBP1 initiates the internalization of AMPARs, a critical step preceding NMDAR-LTD.…”
Section: The Role Of Small Gtpases and Recycling Endosomes In Neuronamentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA and protein analysis demonstrated that REPS2 is predominantly expressed in the central nervous system as compared to other tissues (33,40), being particularly enriched in neuronal populations (33,49). REPS2 has been shown to regulate glutamate receptor endocytosis (33), but no further studies have addressed its role in neuronal function. REPS2 also regulates cell death pathways.…”
Section: Grx1 and S-glutathionylation In Pdreactive Species (Protein mentioning
confidence: 99%